2020
DOI: 10.1108/mip-05-2019-0277
|View full text |Cite
|
Sign up to set email alerts
|

Do materialists care about sustainable luxury?

Abstract: PurposeThe purpose of this study is to investigate the underlying psychological mechanism and boundary conditions which drive materialists' purchase intention (PI) of sustainable over generic luxury products.Design/methodology/approachFour empirical studies (one survey and three experiments) were conducted to test the hypotheses.FindingsMaterialism has a positive effect on consumers' purchase intention of sustainable over generic luxury products because materialists tend to have higher perceived functional val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 47 publications
0
31
3
Order By: Relevance
“…The impression vegan‐leather luxury goods could make on friends and family (De Klerk et al, 2019). Drawing from the work of Jain (2019a, 2019b), Talukdar and Yu (2020), and Ki and Kim (2016), four items relating to perceived quality (PQ) were developed. Three items concerning perceived aesthetics (PA) were adopted from Jung et al (2016), Magnuson et al (2017), and Stępień et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The impression vegan‐leather luxury goods could make on friends and family (De Klerk et al, 2019). Drawing from the work of Jain (2019a, 2019b), Talukdar and Yu (2020), and Ki and Kim (2016), four items relating to perceived quality (PQ) were developed. Three items concerning perceived aesthetics (PA) were adopted from Jung et al (2016), Magnuson et al (2017), and Stępień et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…This trait plays a central role in predicting consumer behavior as highly materialistic attach themselves to worldly possessions (Ellis, 1992;Richins and Dawson, 1992;Richins, 1994;Kilbourne and Pickett, 2008;Goldsmith and Clark, 2012;Shrum et al, 2013). They tend to purchase luxury products to display status-quo (Talukdar and Yu, 2020). Thus, a reputation with the products could lead to a higher purchase intention (Gupta et al, 2020).…”
Section: Materialismmentioning
confidence: 99%
“…Ali et al (2019) discussed the positive relationship between materialism and purchase intention of luxury cars. Talukdar and Yu (2020) have tried to explore the relationship between purchase intention of luxury products along with the dimension of materialism and product conspicuousness. Therefore, materialism comprising possessiveness, non-generosity and envy has a positive impact on purchase intention.…”
Section: Materialismmentioning
confidence: 99%
“…Research in this area has demonstrated that while these two concepts are incongruent to each other (Achabou and Dekhili, 2013), there are some conditions under which consumers are likely to accept sustainable luxury brands (Janssen et al, 2014;Ki and Kim, 2016;Rolling and Sadachar, 2018). Notably, there are consumerrelated factors, including personality trait (Talukdar and Yu, 2020) and gender (Achabou and Dekhili, 2013), and also brand-related factors, including brand conspicuousness (Kumagai, 2020) and marketing communication styles (Amatulli et al, 2020;Septianto et al, 2021). Notably, prior research has suggested that positive emotions such as pride and gratitude might be beneficial to increase online sharing intentions of sustainable luxury contents (Septianto et al, 2021).…”
Section: Sustainable Luxury Brandmentioning
confidence: 99%